1987
DOI: 10.2527/jas1987.651117x
|View full text |Cite
|
Sign up to set email alerts
|

The Crossbred Sire: Experimental Results for Swine

Abstract: Experiments aimed at comparing crossbred and purebred boars were reviewed. These experiments showed that crossbred boars matured sexually more quickly than corresponding purebred boars: they exhibited greater testis weight, large ejaculate volume and had better semen quality. Young crossbred boars were more aggressive sexually and achieved a higher conception rate, particularly on first service. Differences between the two types of boars for litter size and weight were generally small and variable in direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…The lack of paternal heterosis observed in this study seems to be a general fact, as pointed out by recent reviews of Buchanan (1987) and Bidanel (1988). Pani et al (1963) first reported significant grand-maternal effects on litter size at weaning.…”
Section: Introductionsupporting
confidence: 52%
“…The lack of paternal heterosis observed in this study seems to be a general fact, as pointed out by recent reviews of Buchanan (1987) and Bidanel (1988). Pani et al (1963) first reported significant grand-maternal effects on litter size at weaning.…”
Section: Introductionsupporting
confidence: 52%
“…It can therefore be concluded that heterosis was not due to earlier sexual maturity of crossbred bucks but was expressed all along the lifetime investigated. In pigs, heterosis for sperm concentration is not a general rule but it was found in most experiments involving young boars [10], in relationship with heterosis on sexual precocity.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of crossbreeding on semen quality traits is not much documented in domestic animal species, except in pig. In his review, Buchanan [10] concluded that crossbred boars generally exhibited larger ejaculate volume, had better semen quality but results concerning sperm concentration varied depending on the study. In cattle, the review concerning the crossbred sire by Thrift and Aaron [28] yielded only one result for heterosis on semen traits, showing heterosis for concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative models to the widely used Dickerson (1969;1973) Kinghorn (1980Kinghorn ( , 1982 compared different epistatic models differing in the type of gene action. However, the most general and satisfactory model, based on Cockerham's (1954) decomposition of genetic variance in a 2-locus model, was proposed by Hill (1982 Buchanan, 1987;or Bidanel, 1988 Sheridan (1981). More recent evidence of epistatic effects has been provided by Kinghorn (1983) for various growth and reproductive traits in mice, by Koch et al (1985) for survival, pregnancy and marbling score in beef cattle, by Hagger (1986; and Fairfull et al (1987) for egg production and by Ericson and Danell (1986), Syrstad (1988) Hayashi et al, 1978;or Gyllensten et al, 1985).…”
Section: Discussionmentioning
confidence: 99%